2013
DOI: 10.5937/asn1367230m
|View full text |Cite
|
Sign up to set email alerts
|

Quality of air and water in dental healthcare settings during professional toothcleaning

Abstract: Introduction. Professional toothcleaning with ultrasonic scaler pro- 95CI,) CFU/mL and 12.4 (95CI,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Guida et al (2012) and Messano et al (2013) demonstrated that the levels of airborne bacterial contamination inside the dental office during the performance of dental procedures were much higher than the background Table 2 Indoor to background ratios of the particle concentrations during dental procedures.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Guida et al (2012) and Messano et al (2013) demonstrated that the levels of airborne bacterial contamination inside the dental office during the performance of dental procedures were much higher than the background Table 2 Indoor to background ratios of the particle concentrations during dental procedures.…”
Section: Discussionmentioning
confidence: 97%
“…The plates were then incubated aerobically (2 days at 37 1C for bacteria and for 14 days at 28 1C for fungi). The results were expressed in colony forming units per plate (CFU/plate) (Borrego et al, 2012;Messano et al, 2013). The bacterial colonies were characterized by Gram staining and biochemical tests API 20NE and API Staph (bioMerieux, France).…”
Section: Daymentioning
confidence: 99%
“…General Dental Practitioners (GDPs) were contacted before registering to Continuing Medical Education courses, as explained elsewhere 12 , GDPs who had DHs working in their offices were asked to contact them and to invite them to participate to the study. Participation was on a voluntary basis and there were no incentives.…”
Section: Methodsmentioning
confidence: 99%
“…Infectious diseases associated with the biofilm of dental unit waterlines (DUWLs) are RTIs due to Legionella pneumphila, Pseudomonas aeruginosa, Mycobacterium, which are not or minimally contagious and affect immune-compromised individuals with consequently high case-fatality rates. This paper reported that the microorganisms from DUWLs were qualitatively and quantitatively different from the airborne microorganisms, thus suggesting that human microorganisms are likely to be the main source of airborne bacteria in the dental offices 6 . This result does not imply that DUWLs are not a source of airborne microorganisms, as it was previously demonstrated that more than 70% of DUWLs were contaminated by oral streptococci, selective microorganisms of the upper respiratory tract 7 , but only that human microorganisms prevail to bacteria from the aquatic biofilm.…”
Section: Where Does Microbial Contamination Of Air Of Dental Offices mentioning
confidence: 95%